Pengaruh Pembelajaran Daring terhadap Learning Loss dan Implikasinya terhadap Learning Outcome - Ai Nur Solihat; Ati Sadiah; Gugum Gumilar (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
The purpose of this study was to collect data and analyze the effect of online learning on learning loss and its consequences for learning outcomes. This study employs an explanatory survey technique with saturated sampling. This study surveyed 97 students from the Department of Economics Education at FKIP Siliwangi University. To obtain information about the variabels associated with online learning, learning loss, and learning outcomes, descriptive analysis using the SPSS 24 application was used, whereas path analysis using the AMOS application was used to determine the direct and indirect effects of online learning on learning loss and learning outcomes. The results indicated that online learning at the Department of Economics Education FKIP Siliwangi University had a strong categorization tendency, while the learning loss and learning outcome variabels had a moderate categorization tendency. Online learning has a 65.9 percent effect on learning loss and a 67.7 percent effect on learning outcomes.